Burnout dan Mengatasi Keagamaan di Kalangan Akademisi - Abu Hassan Makmun; Damrus Damrus; Yusnaidi Yusnaidi (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2025)
Academics are burdened with supplemental tasks that surpass their main responsibilities of teaching, research, and service. These tasks are often ambiguous and demanding, yet they are rarely beneficial for their career development. This conflicting role may result in burnout. Academics, however, may cope with these demands in numerous ways, including religion. This study examines the influence of teaching and life interference with research (TLR) on burnout, with religiosity as a moderator. The sample was 91 Muslim higher education academics in Indonesia. Hierarchical regression was used for analysis. The results showed the positive effect of TLR on burnout and the buffering effect of religiosity against burnout. However, religiosity did not moderate between TLR and burnout. Policymakers should design policies that reduce the workload of academics, while academics themselves should consider turning to religion to reduce their work stress.